PENGGUNAAN MEDIA PREZI DAN KAHOOT SERTA PEMBERIAN REWARD SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR AKUNTANSI - Siti Zoebaidha (Kwangsan: Jurnal Teknologi Pendidikan, 2020)
Learning by implementing the conventional methods in which the teachers are considered as the learning central attention (teacher-centered learning) and books as the main learning sources is no longer relevant. Since the most students now become more familiar with the development of technology, the teachers are also required to adapt with the technology-based learning. This classroom action research (CAR) was conducted in three cycles (pre-cycle, cycle-1, and cycle-2). The stages and activities made in cycle-1 were similar with those made in cycle-2. The different was only related to development and completion made in cycle-2 due to the weaknesses found in cycle-1. This research aims at revealing the impact of Prezi & Kahoot media and reward’s giving utilized as the learning strategies on the improvement of learning achievements made by the XI Ak 3 students of SMKN-2 Madiun in the academic year of 2018/2019. It is concluded that the utilization of Prezi & Kahoot media and reward’s giving can improve the student’ cognitive learning achievements up to 84%. It means that these learning achievements are already above the Minimum Mastery Criteria (75%) set by the school. ABSTRAK: Pembelajaran menerapkan metode konvensional, guru sebagai pusat pembelajaran (teacher-centered learning), dengan menggunakan buku sebagai sumber belajar dinilai sudah kurang relevan sekarang ini. Hal ini dikarenakan siswa sudah semakin akrab dengan perkembangan teknologi yang ada sehingga guru juga dituntut untuk dapat beradaptasi dan mengadopsi pembelajaran berbasis teknologi. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang berlangsung 3 siklus (pra siklus, siklus-1, dan siklus-2). Tahapan dan kegiatan yang dilakukan pada siklus-1 adalah sama dengan yang dilakukan pada siklus-2. Perbedaannya terletak pada perbaikan dan penyempurnaan pada siklus-2 yang didasarkan atas kekurangan/kelemahan pada siklus-1. Penelitian ini bertujuan untuk mengetahui dampak penggunaan media Prezi dan Kahoot serta pemberian reward sebagai sarana pembelajaran terhadap peningkatan hasil belajar siswa kelas XI Ak 3 SMKN-2 Madiun Tahun Pelajaran 2018/2019. Simpulan penelitian adalah bahwa penggunaan media Prezi dan Kahoot serta pemberian reward dapat meningkatkan hasil belajar kognitif siswa sampai 84%. Capaian ini berarti berada di atas Kriteria Ketuntasan Minimal (KKM) yang ditetapkan sekolah sebesar 75%.